Telecommunications law and regulation in Lesotho: a critical analysis - Lebone, Likonelo (Department of Commercial Law, 2026)
In 2000, the Lesotho telecommunications sector underwent a fundamental change in structure, from that of monopoly to one of competition. A new regulatory regime was introduced and a regulatory agency, the Lesotho Telecommunications Authority was established to promote telecommunications development and to safeguard competition.The 2000 legal framework supports competition but fails to adequately minimise the regulatory risk. The new regime also failed to facilitate improved or satisfactory sector performance. The Lesotho regulatory framework addresses most internationally recognised telecommunications regulatory issues, but most areas needs improvement if sector performance and investor perception is to be enhanced. Firstly, the Government must give the regulatory Authority functional independence. Secondly, the Authority must revisit various policy areas. For instance universal access policy and programmes that bring affordable services to the rural and urban populations alike must be developed and implemented; complimentary policies that encourage the use of the services and investment in the sector, like investment, consumer protection and competition policies must be adopted; alternative dispute resolution mechanisms, especially for disputes between the regulator and service providers must be introduced and preferred in the sector. The challenge is to bring telecommunication services to all communities including low-income families and communities in rural and mountainous areas. Thus whatever policies are adopted, universal access and improved sector performance should be a guiding goal which must be pursued rigorously.